CORTICOSTEROID THERAPY FOR ACUTE ASTHMA : A SYSTEMATIC REVIEW - Aulidaweli, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Asthma is a chronic inflammatory disorder of the airways which affects 300 million people worldwide. Asthma places a huge burden in multiple nations. The main care components for asthma include assessment and monitoring, patient education, addressing environmental controls and comorbid conditions, and pharmaceutical therapy. Corticosteroids therapy is used for maintenance of asthma. While Systemic corticosteroids are often regarded as the first-line treatment for acute asthma since they are unmistakably linked to a quicker recovery to baseline function.The aim: This study aims to show effectiveness of corticosteroid therapy for acute asthma. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and ScienceDirect, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Results: In the PubMed database, the results of our search brought up 60 articles, whereas the results of our search on ScienceDirect brought up 117 articles. The results of the search conducted by title screening yielded a total 15 articles for PubMed and 7 articles for ScienceDirect. We compiled a total of 9 papers, 6 of which came from PubMed and 3 of which came from ScienceDirect. We excluded 1 duplicate article and 1 review article. In the end, we included seven research (RCT) that met the criteria. Conclusion: Corticosteroids therapy, whether oral, intravenous and inhaled, is effective to increase lung function (PEF), improve symptoms, and has fewer side effects. Corticosteroids therapy is also effective to reduce admission or hospitalization rate in severe acute asthma.